Hydraulic Performance Evaluation of Approach Flow Using CFD: A Case Study of Budhi Gandaki Hydroelectric Project (341 MW) - Lakhey, Sanish Raj; Kafle, Mukesh Raj (International Journal on Engineering Technology and Infrastructure Development, 2026)
The hydraulic performance of settling basins in hydropower projects depend greatly on the approach flow conditions. A three-dimensional RANS-based CFD model was validated with field measurements from the Middle Mewa Hydropower Plant (MMHPP) to study these dynamics. The model showed a good correlation in velocity distribution and turbulence characteristics. The validated model was then utilized for two alternate approach-tunnel configurations within the Budhi Gandaki Hydroelectric Project (BGHEP). The results indicate that culvert geometry significantly influences the flow entering the settling basin. The baseline setup (Case 1) made the velocity distribution uneven, the entrance jets very powerful, and the near-bed recirculation very wide. The optimized setup (Case 2), on the other hand, made the flow more even and lowered the intensity of the turbulence. The research shows that for Himalayan hydropower projects to manage hydraulic performance well; the approach canals must be designed correctly. The results also show how useful validated CFD may be as a design tool for improving headworks hydraulics, especially when testing with physical models is not possible.